Physical Activity Guidelines: Global Trends and Korean Perspectives - Yoon-Jung Choi; Jeongran Ko; Junghoon Kim (The Asian Journal of Kinesiology)
Regular physical activity is universally recognized as a cornerstone of good health. Substantial evidence shows that an active lifestyle lowers the risk of major non-communicable diseases and improves mental well-being and overall quality of life. Despite these well-established benefits, physical inactivity remains a pervasive global problem; approximately one in three adults and four in five adolescents fail to meet recommended physical activity levels. Increasing attention focuses on 24-hour movement behaviors, an integrated concept that encompasses physical activity, sedentary behavior, and sleep across a full day. Rather than addressing these behaviors in isolation, recent guidelines advocate a whole-day approach, recognizing that activity, inactivity, and sleep collectively impact health. Evidence shows a clear dose–response relationship, as adhering to recommendations for all three behaviors yields greater health benefits than meeting only one or two. The 24-hour movement framework represents a global shift toward integrated health guidelines that emphasize physical activity, reduced sedentary time, and adequate sleep. In response to high inactivity and sedentary rates, Korea has aligned with this approach through its updated national guidelines. However, translating these recommendations into action requires cultural changes, supportive environments, and multilevel strategies. Future research should investigate how socioeconomic and cultural factors influence adherence to 24-hour movement guidelines in Korea and explore the effectiveness of integrated interventions targeting multiple behaviors simultaneously. Embracing and adapting the 24-hour approach is essential for advancing public health in Korea.